Conductas disruptivas y aprendizaje significativo en estudiantes del nivel secundario de la I.E.P.S.B.I. N° 60265 Yahuma Callarú, distrito de Yavarí 2025 - Avelino Leon, Klariney (2025)
The purpose of this research was to determine the impact of disruptive behaviours on the significant learning of secondary school students at I.E.P.S.B.I. N° 60265 Yahuma Callaru, district of Yavari 2025. The study was of basic type, quantitative approach, correlational level and non-experimental and cross-sectional design. The sample consisted of 85 secondary school students for the survey conducted by means of a questionnaire and a report card for data collection. The findings show that 54.1% of the students are at a moderate level for the variable Disruptive Behaviours, while 47.1% of the students are at a high level for the variable Meaningful Learning. Likewise, Spearman's Rho test showed a significance level of 0.000, which indicates that disruptive behaviours have a significant influence on the meaningful learning of secondary school students at I.E.P.S.B.I. N° 60265 Yahuma Callaru, district of Yavarí 2025.